Murdoch mysteries. Season 05 [videorecording (DVD)] - Bisson, Yannick, 1969-; Jennings, Maureen (Acorn Media, 2013)
Cutting-edge Victorian science meets cunningly plotted mystery in this award-winning Canadian TV drama. William Murdoch is a detective in Toronto in 1895, using new forensic techniques like fingerprinting and psychological profiling. He crosses paths with famous figures including Arthur Conan Doyle, and H.G. Wells.